2010
DOI: 10.1001/archdermatol.2010.265
|View full text |Cite
|
Sign up to set email alerts
|

Chondrodermatitis Nodularis Helicis Successfully Treated With Photodynamic Therapy

Abstract: Chondrodermatitis nodularis helicis (CDNH) is a painful inflammatory condition affecting the helix of the ear. We describe 5 patients with CDNH who were successfully treated with methyl aminolevulinate photodynamic therapy (PDT). REPORT OF CASES Five patients at our clinic, 3 women and 2 men, with a mean age of 77 years (age range, 58-88 years), were diagnosed as having CDNH. All cases presented with 1 or 2 small, painful erythematous nodules, 3 of which were centered by an ulcer, on the upper part of the heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In a report of five patients with radiodermatitis, red light ALA‐PDT induced remission in two and achieved a partial response in three 78 . Four of five patients with chondrodermatitis cleared following one MAL‐PDT treatment using the standard protocol for AK 79 …”
Section: Other Indicationsmentioning
confidence: 99%
“…In a report of five patients with radiodermatitis, red light ALA‐PDT induced remission in two and achieved a partial response in three 78 . Four of five patients with chondrodermatitis cleared following one MAL‐PDT treatment using the standard protocol for AK 79 …”
Section: Other Indicationsmentioning
confidence: 99%
“…Recurrence is often high, and many treatment options have been introduced, including surgical excision, electrodesiccation, pressure-relieving prosthesis, photodynamic therapy, injectable collagen, and topical nitroglycerine. [1][2][3][4][5] The most widely referenced surgical approach is cartilage-only excision, described initially by Lawrence in 1991, 1 with modifications of his method being reported in the literature with equally acceptable results. 6 The fundamentals of this method include removal of diseased cartilage with preservation of skin.…”
Section: Discussionmentioning
confidence: 99%
“…Another relatively new therapy for CNH is photodynamic therapy (PDT). Gilaberte et al first reported the use of PDT in 2010 in a prospective study of five patients who had previously undergone treatment with pressure relieving devices, topical steroids, and cryotherapy with little or no improvement (Gilaberte, Frias, & Pérez‐Lorenz, ). Mean duration of prior treatment was 11.6 months.…”
Section: Therapiesmentioning
confidence: 99%
“…The procedure was tolerated well by all patients with no adverse effects. All lesions resolved except for one, after three treatments spaced 1 month apart (Gilaberte et al, ). Pellegrino et al used PDT for treatment of two patients with CNH.…”
Section: Therapiesmentioning
confidence: 99%